Corrigendum to "Comparing the influence of net and gross anthropogenic land-use and land-cover changes on the carbon cycle in the MPI-ESM" published in Biogeosciences, 11, 4817–4828, 2014 - S. Wilkenskjeld; S. Kloster; J. Pongratz; T. Raddatz; C. H. Reick (Biogeosciences, 2015)
No abstract available.